SURGICAL RESECTION OF BENIGN FIBROUS HISTIOCYTOMA OF THE SPINAL CORD REGION: A RARE CASE REPORT (Vietnam Journal of Community Medicine, 2026)
Benign fibrous histiocytoma is a rare tumor, particularly when it occurs in the spinal region, where it may cause symptoms such as back pain and limb numbness. We report a rare case of a 25-year-old male patient diagnosed with benign fibrous histiocytoma in the thoracic spinal region, presenting with neurological impairment characterized by incomplete paraplegia, inability to ambulate, and sphincter dysfunction. MRI revealed a mass compressing the thoracic spinal cord, with no evidence of metastasis. Histopathological examination confirmed a benign tumor without evidence of malignancy or malignant transformation. The patient underwent successful surgical resection of the lesion without postoperative complications. Recovery was favorable, and the patient remains under regular follow-up.This case highlights the importance of early recognition and timely treatment of benign fibrous histiocytoma, a rare entity that may lead to serious consequences if not accurately diagnosed and appropriately managed.
Keywords: Benign fibrous histiocytoma, spinal cord, surgical resection, histopathological examination, spinal MRI, rare disease.